PENGARUH PERTUMBUHAN ASET, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI DI BURSA EFEK INDONESIA - I Gusti Ayu Putri Sinta Dewi; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
The capital structure indicates how the company finances its operational activities or how the company finances its assets. Companies need funds that come from their own capital and foreign capital. This study aims to determine the effect of asset growth, company size, and profitability on capital structure in pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange. The study population was 10 pharmaceutical sector manufacturing companies listed on the IDX in 2014-2018. The sample in this study were 9 companies which were determined based on purposive sampling technique so that the total sample during 2014-2018 was 45 company units. The analysis tool used is multiple linear regression analysis. The results showed that asset growth had a positive and significant effect on capital structure, firm size and profitability had no effect on capital structure and simultaneously asset growth, company size and profitability had a significant effect on capital structure. Future research is expected to be able to increase the variety of research variables related to capital structure, so that it can increase research references on capital structure.